Ypq3p-dependent histidine uptake by the vacuolar membrane vesicles of Saccharomyces cerevisiae. Issue 6 (2nd June 2016) - Manabe, Kunio; Kawano-Kawada, Miyuki; Ikeda, Koichi; Sekito, Takayuki; Kakinuma, Yoshimi
Abstract: The vacuolar membrane proteins Ypq1p, Ypq2p, and Ypq3p of Saccharomyces cerevisiae are known as the members of the PQ-loop protein family. We found that the ATP-dependent uptake activities of arginine and histidine by the vacuolar membrane vesicles were decreased by ypq2 Δ and ypq3 Δ mutations, respectively. YPQ1 and AVT1, which are involved in the vacuolar uptake of lysine/arginine and histidine, respectively, were deleted in addition to ypq2 Δ and ypq3 Δ. The vacuolar membrane vesicles isolated from the resulting quadruple deletion mutant ypq1Δypq2 Δ ypq3 Δ avt1 Δ completely lost the uptake activity of basic amino acids, and that of histidine, but not lysine and arginine, was evidently enhanced by overexpressing YPQ3 in the mutant. These results suggest that Ypq3p is specifically involved in the vacuolar uptake of histidine in S. cerevisiae . The cellular level of Ypq3p-HA 3 was enhanced by depletion of histidine from culture medium, suggesting that it is regulated by the substrate. Graphical abstract: : ATP-dependent uptake of histidine but not lysine and arginine into vacuolar membrane vesicles was increased by YPQ3 overexpression.